Contextual obstacles to the delivery of effective psychological treatment of PTSD in a South African community setting - Swartz, Kerry (Rhodes University, Faculty of Humanities, Department of Psychology, 2008)
The present study presents three individual cases; all three clients had endured a traumatic event, namely rape, and all three met the criteria for PTSD. Despite the fact that each of the clients was initially assessed as being a suitable candidate for psychological treatment, none of the cases proceeded to the therapy phase of treatment. A number of obstacles, both personal and contextual, were encountered during treatment implementation, preventing or limiting a successful outcome of psychological treatment in each case. An examination of these cases highlights a few of the many obstacles frequently faced when delivering psychological treatment to the South African context. In so doing, this research provides an opportunity to consider the possible reasons for the limited documentation of treatment efficacy within the South African context, as well as to enhance our understanding of and sensitivity towards the cultural and contextual factors playing a role in psychological treatment.
Keywords: Post-traumatic stress disorder -- Treatment -- South Africa; Rape victims -- Counseling of -- South Africa; Psychic trauma -- Treatment; HIV infections -- South Africa